026 The walton centre integrated neurology nurse service. Issue 12 (14th November 2019) - Fletcher, Nicholas; Vallance, Lydia; Riley, Julie; Nicolson, Andrew; Wilson, Martin
Abstract : A training program was developed for an integrated neurology nurse service (INNS) dealing with common issues in long term neurological conditions, particularly Parkinson's disease, MS, epilepsy and MND. After a successful pilot scheme, the INN team was increased from one to seven nurses. From 2017 to 2018, 1452 patients were seen in INN community clinics and 937 at home. Each week, INNs provided 34 clinics at 27 community locations plus 13 telephone clinics and (where necessary) domiciliary and care/nursing home visits. INNs also visit 7 local A&E departments to advise on pathway utilisation, neurological management and offer clinical review of frequent neurological attenders. Training (for example emergency management of seizures) is also provided in the community. INNs liaise with other agencies regarding social care, appliances, physiotherapy, occupational therapy, speech and language therapy, continence services or district nursing. They can also quickly obtain advice from the patient's WCFT consultant. The INNS was well received; 96% of patients were satisfied or very satisfied with their experience; 67% that the INNS empowered them to make decisions about their health care; 86% that the INNS strengthened shared decision making; 96% reported increased physical and emotional support and 82% that the INNS helped communication between patients and specialist neurology nurses. INNs can work effectively in the community to support patients and reduce demand on primary and secondary care.